PENINGKATAN PRESTASI BELAJAR BIOLOGI SISWA KELAS X.1 SMA N 2 SALATIGA MELALUI METODE PROYEK DENGAN PENILAIAN PRESENTASI DAN POSTER - Purwaningsih, Siti (Universitas Negeri Semarang, 2009)
Implementing the discussion method in studying the topic of Biology,especially in learning about the environment, leaves students unable to apply in reallife what they have learned in school. Because of that, in this research, the ProjectMethod through group work was used in the task of recycling both organic aninorganic waste. The goal of this research was to enhance the students’ affective,cognitive, and psychomotor ability. The research Project took the form of class actionresearch carried out in two cycles, both of which consisted of planning, implementing,observing, and reflection. The results of the research showed that by implementing theProject Method, the ability of the students increased in all three aspects: the cognitiveaspect as evidenced by the daily test scores, the affective aspect as was apparent in thestudents initiative in making posters to raise environmental awareness, and in thepsychomotor aspect made clear by the recycled products that were produced.Kata kunci: prestasi belajar biologi, metode proyek, daur ulang limbah